Ornithine-A urea cycle metabolite enhances autophagy and controls Mycobacterium tuberculosis infection - Ramya Sivangala Thandi (Nature Portfolio, 2020)
Kupffer cells are more resistant to M. tuberculosis when compared with alveolar macrophages. Here the authors show that this distinction is caused by the presence of ornithine and imidazole in Kupffer cells and that these metabolites can drive autophagy and M. tuberculosis killing in alveolar macrophages when given intranasally to infected mice.